Implementasi dan Problematika Kurikulum Merdeka: IMPLEMENTASI DAN PROBLEMATIKA KURIKULUM MERDEKA - Habib, Habib; Eliyah, Eliyah; Hasanah, Mauizatul (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2023)
The Free Learning Policy and Merdeka Curriculum are aimed at improving the quality of education evenly across Indonesia. However, their implementation faces various challenges due to geographical conditions, lack of readiness among teachers and schools. The objective of this literature review is to map the issues in the implementation of the Merdeka Curriculum and formulate alternative solutions. Data sources are derived from articles and journals on the evaluation of the Merdeka Curriculum. The analysis technique employs Miles and Huberman's model, including data reduction, data presentation, and drawing conclusions. The study results identify the main problems as limited understanding and abilities of teachers, as well as inadequate learning facilities. It is recommended to improve curriculum implementation management by involving collaboration among various stakeholders consistently, so that the goals of enhancing the quality and accessibility of education can be achieved